ROLE OF AYURVEDIC DOCTORS IN HEALTH SYSTEM OF NORTH-EAST INDIA IN THE MANAGEMENT OF LIFESTYLE DISEASES - Ahmed, *Taufique; Medhi, Champak (International Journal of Ayurveda and Pharma Research, 2017)
Common lifestyle diseases in India are Diabetes, Arteriosclerosis, Heart diseases, Hypertension, Swimmers Ear, malignancy, stroke, Chronic Obstructive Pulmonary diseases (COPDs), Cirrhosis, Nephritis, Hemorrhoids, Fissure-in-Ano etc. Incidence of patient of above said diseases day by day in India as well as different states of North-east India. Due to change of dietary habits, lifestyle, geo-environmental factors, less public awareness and poor early detection facilities of cases in healthcare of Northeast make the Scenario more worsen. Ayurveda is very much rich in preventing these Lifestyle Diseases and for its management. Ayurveda provides better solution in the forms of proper dietary management, lifestyle advises, Panchakarma like detoxification and bio-purification procedures, medicaments, and rejuvenation therapies. The holistic approach of Ayurveda, treating the patient as a whole, meaning intervention targeted toward complete physical, psychological, and spiritual well-being makes this science a wonderful option in lifestyle disorders. So, the Ayurvedic doctors posted in different health institutions of different states of Northeast India may be used for public awareness program regarding the different regiments of Dinacharya, Ritucharya, Sadvritta, Nidra etc. Ayurvedic treatment.